Associations of sickness absence and disability pension due to mental and somatic diagnoses when aged 60-64 with paid work after the standard retirement age; a prospective population-based cohort study in Sweden - Aleksiina Martikainen; Alice Svensson Alavi; Kristina Alexanderson; Kristin Farrants (BMC, 2021)
Abstract Background The proportion of people working beyond age 65 is increasing. We aimed to explore whether sickness absence (SA) and disability pension (DP) due to mental, somatic, or both diagnoses when aged 60-64 were associated with being in paid work when aged 66-71. Methods This prospective population-based cohort study included all 98,551 individuals who in 2010 turned 65 years, lived in Sweden, and were in paid work at some point when aged 60-64. Data from three nationwide registers were used with 2010 as baseline, with SA or/and DP as the exposure variables (2005-2009) and paid work as the outcome variable (2011-2016). Logistic regression was conducted to calculate odds ratios (OR) with 95% confidence intervals (CI) for the association between exposures and outcome, controlling for sociodemographic factors. The analyses were also stratified by sex. Results Nearly half were in paid work during follow-up. Those with SA due to mental diagnoses had lower likelihood of being in paid work among both sexes (women OR: 0.76; 95% CI: 0.69-0.84; men 0.74; 0.65-0.84), while this association was smaller for SA due to somatic diagnoses (women 0.87; 0.84-0.91; men 0.92; 0.89-0.96). SA due to both mental and somatic diagnoses was associated with a lower likelihood of paid work for men (0.77; 0.65-0.91), but not women (0.98; 0.88-1.09). Regardless of diagnosis group and sex, DP had the strongest association with not being in paid work (women mental DP 0.39; 0.34-0.45; women somatic DP 0.38; 0.35-0.41; women mental and somatic DP 0.28; 0.15-0.56; men mental DP 0.36; 0.29-0.43; men somatic DP 0.35; 0.32-0.38; men mental and somatic DP 0.22; 0.10-0.51). Combined SA and/or DP demonstrated ORs in-between the diagnosis groups of SA and DP alone (e.g., mental SA and/or DP women and men combined 0.61; 0.57-0.65). Conclusions SA and DP were negatively associated with being in paid work after the standard retirement age of 65. The association was especially strong for DP, irrespective of diagnosis group. Moreover, compared to somatic diagnoses, SA due to mental diagnoses had a stronger association with not being in paid work. More knowledge is needed on how mental SA impedes extending working life.